Hepatobiliary Adverse Reactions during Treatment with Cladribine: Analysis of Data from the European Spontaneous Reporting System - Elena Mirabela Velișcu; Valerio Liguori; Antonietta Anatriello; Giorgia Teresa Maniscalco; Andrea Cantone; Luigi Di Costanzo; Pasquale Stefanelli; Cristina Scavone; Annalisa Capuano (MDPI AG, 2023)
Background. Cladribine belongs to the group of disease-modifying therapies (DMTs) used to treat multiple sclerosis (MS). According to the highlights of a meeting held by the Pharmacovigilance Risk Assessment Committee (PRAC) on 14 January 2022, cladribine may be associated with the occurrence of liver injury, and thus liver function monitoring is recommended. Objectives and methods. Using data from the European spontaneous reporting database (EudraVigilance-EV), we aimed to describe the main characteristics of Individual Case Safety Reports (ICSRs) reporting cases of hepatobiliary disorders related to cladribine. The reporting odds ratio (ROR) was calculated to provide the probability of reporting hepatobiliary ICSRs among DMTs used to treat MS. Results. Overall, 118 ICSRs described the occurrence of cladribine-induced hepatobiliary ADRs. The majority of the ICSRs reported ADRs that were classified as serious (93%), and the outcome was mostly reported as "unknown" (50.8%). The most reported hepatobiliary disorders were drug-induced liver injury, abnormal hepatic function, ALT increases, liver disorders, hepatic failure, jaundice, lymphocyte count decreases, hepatotoxicity and hypertransaminasemia. The majority of cladribine-induced hepatic ADRs occurred in female patients belonging to the age group of 18-65 years. Conclusion. Considering the seriousness of cladribine-induced hepatic ADRs, a close monitoring of patients receiving this drug is highly recommended. In this context, further pharmacovigilance studies evaluating the hepatic safety profile of cladribine are strongly needed.